Competitiveness of the Mexican red tomato in the international market: analysis 2003-2017 - Montaño Méndez, Iliana Enriqueta; Valenzuela Patrón, Iván Narcizo; Villavicencio López, Kennia Valeria (Revista Mexicana de Ciencias Agrícolas, 2021)
In Mexico, the agro-livestock sector contributes about 3.4% of the national GDP, with horticultural activity standing out with 45% of the exports of the sector, where the red tomato represents 8.41%. Mexico is the main supplier of this product worldwide, with a share of 19% of world exports, above Spain or the Netherlands. The objective is to determine the competitiveness of the Mexican red tomato in the international market through the relative export advantage (RXA) and constant market share (CMS). Competitiveness of the Mexican product in the US market and a high market concentration were found, sending 98% of Mexican red tomato exports to that destination.
Keywords: agricultural product; competitiveness; exports; market